THE RELATIONSHIP BETWEEN PT. BANK UMKM JAWA TIMUR BRANCH BATU CITY ON DEVELOPMENT SMALL BUSINESS IN BATU CITY - Kusumah, Drajat Wiryo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
PT. Bank UMKM JawaTimur has a strategic correlation in overcoming the problems faced by small business actors in the city of Batu. This research aims to determine the magnitude of the correlation of PT. Bank UMKM JawaTimur branch of Batu City to the development of small business in the city of Batu and to know the implementation of strategies in achieving the development of small business in the city of Batu. The research method used is statistical method of correlation product moment, the result of statistical calculation of correlation product moment obtained by 0,86, this means if interpreted in correlation coefficient table shows strong correlation level, means that capital channeled to small entrepreneur can develop effort through increasing amount of production.Keywords: Correlation Product Moment, capital, development of small business